ANALISIS EFEKTIVITAS KELAS UNGGULAN TERHADAP PENGORGANISASIAN PEMBELAJARAN FISIKA DI SMA NEGERI 2 METRO - Riswanto; Dedy Hidayatullah Alarifin; Ananda Purnomo; Tia Meylan Anggraeni; Yulia Puspita Dewi; Puja Tria Oktaviani; Velicia Septiana (Universitas Muhammadiyah Metro, 2024)
Abstract : The purpose of this study is to identify the causes that contribute tophysics learning with the application of superior classes at SMA Negeri 2 Metro,especially in the learning process. The implementation of superior classes is astrategy in education whose purpose is to provide optimal, intensive, and in-deptheducational services to students who have high academic potential. Some of theproblems identified include low understanding of physics concepts, low studentinterest in physics, and low student learning achievement in this subject. In aneffort to address these issues and improve the quality of physics learning, flagshipclasses were introduced as a potential solution. The method used was to collectdata through classroom observations, teacher and student interviews. Thepurpose of this study was to obtain maximum understanding related to the impactof the implementation of the flagship class. The discussion in this study highlightsthe importance of excellent classes as an effective strategy in organizing physicslearning. In the flagship class, students get a more interesting and interactivelearning experience, which helps them understand physics concepts better. Inaddition, good support and motivation from physics teachers are also factors thatplay a role in the effectiveness of superior classes. Based on the research results,the conclusion is that the featured class has high effectiveness in organizingphysics learning at SMA Negeri 2 Metro. Therefore, it is recommended that schoolscontinue to improve and develop excellent classes as an effort to improve thequality of physics learning. Increasing the application of supporting technology inphysics learning can also be a suggestion to optimize the effectiveness of superiorclasses.